(untitled) (Economics and region, 2023)
The purpose of the study is a comprehensive analytical assessment of international trade in services between Ukraine and EU countries. At the first stage, using the ABC analysis method, 27 EU countries are divided into three groups depending on their share in the total export of services from Ukraine in 2021. At the second stage, using the ABC analysis method, all EU countries are divided into three groups depending on their share in the total import of services to Ukraine in 2021. At the third stage, a structural analysis of export-import transactions with services between Ukraine and those EU countries, which in the previous two stages were twice included in group A (Germany, Poland, Cyprus, the Netherlands, Malta, Austria, France, Denmark, Belgium) was conducted. The services that have the greatest potential for export/import between Ukraine and these countries have been identified.